2018
DOI: 10.5194/amt-11-4015-2018
|View full text |Cite
|
Sign up to set email alerts
|

Ice particle sampling from aircraft – influence of the probing position on the ice water content

Abstract: Abstract. The ice water content (IWC) of cirrus clouds is an essential parameter determining their radiative properties and thus is important for climate simulations. Therefore, for a reliable measurement of IWC on board research aircraft, it is important to carefully design the ice crystal sampling and measuring devices. During the ML-CIRRUS field campaign in 2014 with the German Gulfstream GV HALO (High Altitude and Long Range Research Aircraft), IWC was recorded by three closed-path total water together wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 37 publications
2
50
1
Order By: Relevance
“…The coordinated flight with orbits of the CALIPSO satellite provided an unprecedented opportunity to validate the spaceborne CALIOP lidar with independent high spectral resolution observations by the airborne WALES lidar for an improved PSC classification. Nitric acid containing particles were observed at flight altitude-however, a quantification of the particle sizes and the amount of HNO 3 contained is challenging because of uncertainties due to the enrichments in the inlets (Afchine et al 2018). Extensive denitrification in the lower stratosphere and a nitrification at lower altitudes were observed throughout the winter (Khosrawi et al 2017;Braun et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The coordinated flight with orbits of the CALIPSO satellite provided an unprecedented opportunity to validate the spaceborne CALIOP lidar with independent high spectral resolution observations by the airborne WALES lidar for an improved PSC classification. Nitric acid containing particles were observed at flight altitude-however, a quantification of the particle sizes and the amount of HNO 3 contained is challenging because of uncertainties due to the enrichments in the inlets (Afchine et al 2018). Extensive denitrification in the lower stratosphere and a nitrification at lower altitudes were observed throughout the winter (Khosrawi et al 2017;Braun et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…m L16 (D) is based on a m − D relation by Mitchell et al (2010), which has been slightly modified to improve the representativeness of the mass concentration for small ice crystals. The validity of this type of approach, and of m L16 (D) in particular, was recently consolidated by Erfani and Mitchell (2016) and Afchine et al (2018), who demonstrated their accuracy and generalizability for all types of ice clouds from T c < −20 • C. Afchine et al (2018) in particular has shown that this relation should be applicable to tropical clouds and that the influence of different m − D relations on IWC is small in the temperature range of cirrus clouds. Considering this, and because Mitchell et al (2010) and Erfani and Mitchell (2016) developed and tested their m − D relation using 2D-S measurements from tropical and midlatitude campaigns (including SPARTICUS), m L16 (D) should also be applicable to SPARTICUS and ATTREX2014.…”
Section: Data Processingmentioning
confidence: 99%
“…Indeed, provided that a PSD is properly estimated, the corresponding number concentration (the zeroth moment of the PSD, or M 0 ) can be extracted. Important developments regarding applying these methods to satellite observations can be attributed to Austin and Stephens (2001) who, through an elaborate variational scheme, used the sensitivity of radar reflectivity (Z e ) and τ c to other moments, namely M 6 and M 2 , respectively, to constrain PSD shape parameters. This method, initially dedicated to liquid clouds, allowed for the retrieval of profiles of droplet geometric mean radius and a vertically homogeneous N d .…”
Section: Introductionmentioning
confidence: 99%
“…2 could be responsible for this high sensitivity, due to an overestimated cloud lifetime effect. This is a common problem in coarse-resolution global models, which are not able to resolve the enhanced entrainment of dry air in clouds with higher CDNC, which would lead to droplet evaporation and thus partly offset the CDNC-induced increase in cloud lifetime (Ackerman et al, 2004;Xue and Feingold, 2006;Jiang et al, 2006;Altaratz et al, 2008;Mülmenstädt et al, 2019). Other studies show that the choice of the tuning parameters can also determine the resulting aerosol ERF: Hoose et al (2009) and Neubauer et al (2019) found a smaller (i.e., less negative) aerosol ERF when increasing CDNC min from 10 cm −3 (−1.7 W m −2 ) to 40 cm −3 (−1.0 W m −2 ) in the ECHAM6 model, while Golaz et al (2011) reported a linear dependency of the aerosol radiative flux perturbation on the autoconversion threshold radius in the GFDL AM3 model.…”
Section: Anthropogenic Aerosol Erfmentioning
confidence: 99%